#TITLE_ALTERNATIVE# - AZKA AULIA NADHIRA (NIM : 10209099),
One of geophysical methods that can be used to analyze the physical feature of earth-subsurface layer is gravity method. This method is corresponded with the variation of gravitational field. Sometimes, an analytical calculation does not give satisfying information regarding the physical feature of earth-subsurface layer. In that case, forward and inverse modeling shall be done to describe the earth physical feature and gravity anomaly response. In this thesis, these modeling are created by assuming a certain shape of anomaly, which will be presented in two dimensions.